The antibacterial activity of propolis produced by Apis mellifera L. and Brazilian stingless bees - Fernandes Jr., A. [UNESP]; Leomil, L. [UNESP]; Fernandes, A.a.h. [UNESP]; Sforcin, J.m. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2001)
This study investigated the antibacterial activity of propolis produced by A. mellifera and Brazilian stingless bees, called meliponíneos. Susceptibility tests to ethanolic extracts of propolis (EEP) were performed using bacterial strains (Staphylococcus aureus, Enterococcus sp, and Escherichia coli) isolated from human infections. Dilution of EEP in agar (%v/v) was used for determination of minimal inhibitory concentration (MIC). The stingless bee species (and common names) were: Nannotrigona testaceicornis (Iraí), Tetragonisca angustula (Jataí), Trigona spinipes (Arapuá), Scaptotrigona sp (Tiúba), Partamona sp (Cupira), Melipona scutellaris (Uruçu), Melipona sp (Manduri), and Melipona mandaçaia (Mandaçaia). EEP inhibitory efficiencies according to bacterial strains were: S. aureus - Cupira > Manduri = A. mellifera > Uruçu > Mandaçaia > Iraí > Tiúba > Jataí > Arapuá = Ethanol; Enterococcus sp - Cupira > Manduri > A. mellifera > Mandaçaia > Uruçu > Tiúba > Jataí > Arapuá = Ethanol; E. coli - Manduri > Jataí > Ethanol > A. mellifera > Uruçu > Cupira > Iraí. Propolis produced by Cupira and Manduri bees showed higher antibacterial activity than A. mellifera.
Keywords: Ethanolic extract of propolis; Apis mellifera; Brazilian stingless bees; S. aureus; E. coli; Enterococcus sp